How do third sector organisations or charities providing health and well-being services in England implement patient-reported outcome measures (PROMs)? A qualitative interview study. Issue 10 (7th October 2020) - Foster, Alexis; O'Cathain, Alicia; Harris, Janet
Abstract : Objectives: To identify the facilitators and barriers to implementing patient-reported outcome measures (PROMs) in third sector organisations (TSOs) delivering health and well-being services. Design: A qualitative interview study. Participants were recruited using purposive, opportunistic and snowballing methods. Framework analysis was used. Setting: TSOs including charities, community groups and not-for-profit organisations in England, UK. Participants: Thirty interviewees including service users, TSO front-line workers and managers, commissioners of TSOs and other stakeholders such as academic researchers. Results: TSOs primarily used PROMs because of pressures arising from the external funding context. However, organisations often struggled to implement PROMs, rarely getting the process right first time. Facilitators for implementation included having an implementation lead committed to making it work, investing resources in data management systems and support staff and taking a collaborative approach to designing the PROMs process. The latter helped to ensure an appropriate PROMs process for the specific TSO including choosing a suitable measure and planning how data would be collected, processed and used. There was a dilemma about whether TSOs should use standardised well-being measures (eg, the Warwick-Edinburgh Mental Well-being Scale) or design their own PROM. Not all TSOs sustained the collection and reporting of PROMs over time because this required a change in organisational culture to view PROMs as beneficial for the TSO and PROMs becoming part of front-line workers' job specifications. Conclusions: TSOs are trying to use PROMs because they feel they have no choice but often struggle with implementation. Having an implementation lead, designing an appropriate process, investing resources, training staff and taking mitigating action to address potential barriers can facilitate implementation. Some of the findings are consistent with the experiences of more clinical services so appear relevant to the implementation of PROMs irrespective of the specific context.